Analysis of Differences in Audits with Recency Patterns and Audits Without Patterns on Tax Compliance - Fithiyaturrahmah Fithiyaturrahmah; Muslimin Muslimin (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The purpose of this research is to examine analysis of differences in audits with recency patterns and audits without patterns on tax compliance. This study uses a quantitative approach using primary data. The data in this study were obtained using the experimental method. Students who participate in this study consist of several criteria to support the success of the experiment, first, students must come from the economics and business faculties with bachelor, master, and doctoral education levels. Second, students have completed taxation courses and have general knowledge of taxation. Thus, students who act as taxpayers will be able to fulfill the scenario in answering the research questions. Hypothesis testing is carried out to provide answers to problems in the research that has been prepared. The test tool used for each hypothesis in this study is the mann-whitney test. The results show that there is differences between audits with recency patterns and audits without patterns on tax compliance.